Effect of milling time variation on TiTaVWCr HEA powder as nuclear material on microstructure and mechanical properties by a mechanical alloying method. Issue 1 (1st March 2023) - Sutrisna,; Prasetiyo, A B; Kartikasari, R; Aziz, I
Abstract: TiTaVWCr HEA alloy is a refractory material that is often used as nuclear material. This research uses powder material and milling using the mechanical alloy method. This research aimed to determine the microstructure and mechanical properties of the TiTaVWCr HEA alloy milling process for 4 h, 8 h, 16 h, and 24 h. Tests were carried out using XRD spectra and Secondary Electron Microstructure-Energy Dispersive Spectroscopy (SEM-EDS) to determine the characteristics of the material and its microstructure. The results showed that the HEA model with low milling (4 h and 8 h) microstructure distribution was not uniform, and there was agglomeration in certain areas. After milling was increased to 16 hours, the distribution of elements became uniform, but oxides appeared on Ti became in the formation of Ti-O. The hardness value shows that the longer the milling time, the higher the hardness. This phenomenon is related to the increase in grain dimension, and dislocation density.